Efficacy of modified diode transscleral cyclophotocoagulation in patients with painful neovascular glaucoma secondary to retinal vein occlusion - O.V. Guzun; O.S. Zadorozhnyy; I.O. Nasinnyk; A.R. Korol (Journal of Ophthalmology)
Purpose: To assess the efficacy (success rate) of modified diode transscleral cyclophotocoagulation (TSCPC) in patients with painful neovascular glaucoma (NVG) secondary to retinal vein occlusion (RVO).